Selective CO2 and H-2 adsorption in a chiral magnesium-based metal organic framework (Mg-MOF) with open metal sites - Mallick, Arijit; Saha, Subhadeep; Pachfule, Pradip; Roy, Sudip; Banerjee, Rahul (Journal of Materials Chemistry, 2010)
A rare porous magnesium-based metal-organic framework, Mg-MOF-1 [Mg(3,5-PDC)(H2O)], was synthesized solvothermally in DMF. Structural determination by X-ray single-crystal diffraction technique reveals that this chiral MOF (space group P6(1)22) is constructed by helical assembly of Mg2+ ions with achiral 3,5-pyridine dicarboxylates and coordinating water molecules, to form a three-dimensional framework with parallel hexagonal channels. The structural detail of its 0D analogue Mg-MOF-2 [Mg(2,4-PDC)(H2O)(3)] has been discussed to show how subtle variation in the ligand architecture changes the resulting structure from 0D to 3D. Mg-MOF-1 remains robust and porous upon evacuation of the coordinating water molecules. This is the first report of a chiral hexagonal Mg-MOF synthesized from an achiral organic building unit. Open Mg metal sites show selective hydrogen (H-2) adsorption (ca. 0.8 wt% at 77 K) and carbon dioxide (CO2) uptake (ca. 0.7 mmol g(-1) at 298 K) over nitrogen at 1 atm. Ab initio quantum chemical calculation of adsorption energies and possible adsorption sites of hydrogen molecules are also reported.

Structural diversity in a series of metal-organic frameworks (MOFs) composed of divalent transition metals, 4,4 `-bipyridine and a flexible carboxylic acid - Pachfule, Pradip; Panda, Tamas; Dey, Chandan; Banerjee, Rahul (Crystengcomm, 2010)
A series of flexible metal-organic frameworks (MOFs) have been successfully synthesized under hydrothermal condition using 1,3-adamantanediacetic acid (C(14)H(20)O(4), H(2)ADA) as a flexible dicarboxylate building block, 4,4'-bipyridine and transition metal ions [Cd(II), Zn(II), and Mn(II)] as metal centers in DMF and aqueous media. These MOFs formulated as [Cd(ADA)(4,4'-bipy)(0.5)]center dot(DMF) (Cd-ADA-1), [Mn(ADA)(4,4'-bipy)(0.5)]center dot(DMF) (Mn-ADA-1), Zn(ADA)(4,4'-bipy)(0.5) (Zn-ADA-1), and [Mn(HADA)(2)(4,4'-bipy)(H(2)O)(2)] (Mn-ADA-2) (ADA = 1,3-adamantanediacetate, 4,4'-bipy = 4,4'-bipyridine and DMF = N,N'-dimethyl formamide) display interesting 1D, 2D and 3D structural features depending on the solvent of synthesis. All these MOFs were structurally determined by single-crystal X-ray diffraction. The coordination modes of this ligand are discussed and in addition, thermal stability and hydrogen (H(2)) and carbon-dioxide (CO(2)) adsorption properties of Cd-ADA-1, Mn-ADA-1 and Zn-ADA-1 are also presented. Hydrogen sorption at 77 K and up to 1 atm is found to be 0.42, 0.72 and 1.36 wt% without saturation for Zn-ADA-1, Mn-ADA-1 and Cd-ADA-1 samples.

Structural diversity in partially fluorinated metal organic frameworks (F-MOFs) composed of divalent transition metals, 1,10-phenanthroline, and fluorinated carboxylic acid - Pachfule, Pradip; Dey, Chandan; Panda, Tamas; Vanka, Kumar; Banerjee, Rahul (Crystal Growth & Design, 2010)
Seven new partially fluorinated metal-organic frameworks (F-MOFs) have been synthesized under different solvothermal conditions (H(2)O or N,N-dimethylformamide (DMF)) from transition metal cations [Zn(II), Co(II), and Mn(II)], 1,10-phenanthroline (phen), and 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C(17)H(10)F(6)O(4), H(2)hfbba) to determine the influence of reaction conditions on the formation of metal-organic frameworks. This family of materials displays a striking degree of structural similarity depending on the solvent of synthesis. Of the seven materials, two contain three-dimensional connectivity: Co(3)(hfbba)(6)(phen)(2) (F-MOF-6) and Mn(3)(hfbba)(6)(Phen)(2) (F-MOF-10). Three materials are one-dimensional structures: Zn(hfbba)(0.5)(phen)(HCO(2)) (F-MOF-8), Mn(Hhfbba)(2)(Phen) (F-MOF-11), and [Mn(hfbba)(2)(dm-phen)]center dot(H(2)O) (F-MOF-11A). Lastly, Co(hfbba)(phell)(2)center dot 2(H(2)hfbba)(H(2)O)(HCO(2)) (F-MOF-7) and Zn(hfbba)(phen)(2)center dot 2(H(2)hfbba) (H(2)O)-(HCO(2)) (F-MOF-9) are discrete zero-dimensional molecular complexes. F-MOF-6 and -10, which feature it three-dimensional (3D) framework with pcu topolgy are formed in DMF like F-MOF-8 and at 85 degrees C. The remaining F-MOFs are formed by a solvothermal reaction at 120 degrees C in water. F-MOF-7 and -9 are isostructural discrete zero-dimensional molecular complexes (a similar to 19.5; b similar to 13.7; c similar to 26.2/29.6 angstrom; beta similar to 99.9/120.04; V similar to 6840 angstrom(3)). All these F-MOFs were structurally determined by single-crystal X-ray diffraction. Solid-state properties such its UV-vis and the thermal stability of F-MOF-6 to -11A have also been studied. Insight into the factors influencing the preferred crystallization of a specific complex over others has been obtained from full quantum chemical (QM) calculations using density functional theory (DFT).

Structural, magnetic, and gas adsorption study of a two-dimensional tetrazole-pyrimidine based metal-organic framework - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2010)
A new two-dimensional (2D) metal-organic framework, Cu-TP-1, has been synthesized under solvothermal conditions (DMF) from the transition metal cation Cu(II) and 2-tetrazole pyrimidine (C5H5N6, H-TP). The structure has been determined by single crystal X-ray crystallography which shows a (6,3) honeycomb 2D net with perpendicular one-dimensional channels. Permanent porosity of Cu-TP-1 has been determined by the nitrogen adsorption isotherm. Cu-TP-1 show interesting H-2 and CO2 uptake. CO2 uptake of Cu-TP-1 (at 298 K, 1 atm pressure) is seen to be comparable to the recently reported ZIF-95 which outperforms ZIF-100 and BPL carbon. The magnetic properties show an antiferromagnetically coupled Cu ... Cu interaction down to 8 K with a Weiss temperature around 108 K.

Synthesis and structural comparisons of five new fluorinated metal organic frameworks (F-MOFs) - Pachfule, Pradip; Dey, Chandan; Panda, Tamas; Banerjee, Rahul (Crystengcomm, 2010)
A series of fluorinated metal-organic frameworks (F-MOFs) have been successfully synthesized under hydrothermal condition using 4,40-(hexafluoroisopropylidene) bis(benzoic acid) (C(17)H(10)F(6)O(4), H(2)hfbba) as a flexible dicarboxylate building block, Cu(+2) and various heterocyclic co-ligands. These F-MOFs formulated as [Cu(hfbba)(phen)(2)]center dot 2(H(2)hfbba)(H(2)O)(HCO(2)) (F-MOF-1), [Cu(hfbba)(2)(2,2'-bipy) 2(H(2)O)] (F-MOF-2), [Cu(hfbba)(4,4'-dime-2,2'-bipy)(HCO(2))]center dot(hfbba)(H(2)O) (F-MOF-3), [Cu(2)(hfbba)(2)(3-mepy)(2)]center dot(DMF) 2(3-mepy) (F-MOF-4), and [Cu(hfbba)(2)(phen)(2)]center dot 0.5(DMF) (F-MOF5) (hfbba = 4,4'-(Hexafluoroisopropylidene) bis(benzoate), phen 1,1'-phenanthroline; 2,2'-bipy 2,2'-bipyridine; 4,4'dime-2,2'-bipy 4,4'-dimethyl 2,2'-bipyridine; 3-mepy 3-methyl-pyridine and DMF dimethyl formamide) display interesting H-bonded, 1D and 2D structural features. All these F-MOFs were structurally determined by single-crystal X-ray diffraction. F-MOF-1 and 5 form a distorted octahedral Cu(+2) secondary building unit (SBU). F-MOF-5 forms a one-dimensional architecture constructed from Cu(2+) ions bridged by phen anions and two types of 4 hfbba ligands while in F-MOF-1, two among the three acid co-ligands are not coordinated with Cu(2+) ions. F-MOF-2 displays dinuclear SBUs within the three-dimensional frameworks whereas F-MOF-3 displays mononuclear SBUs and forms a one-dimensional chain. F-MOF-4 display a interesting 2D framework with conventional Cu(2)(CO(2))(4) paddle wheel SBU. In the crystal structures four hfbba ligands, each coordinated to a dicopper paddlewheel unit via one of their carboxylate groups. Solid-state properties such as UV-vis and thermal stability of F-MOF-1-5 have also been studied.

Selectivity tailoring in liquid phase oxidation over MWNT-Mn3O4 nanocomposite catalysts - Biswal, Mandakini; Dhas, Vivek V.; Mate, Vivek R.; Banerjee, Abhik; Pachfule, Pradip; Agrawal, Kanika L.; Ogale, Satishchandra B.; Rode, Chandrashekhar V. (Journal of Physical Chemistry C, 2011)
Highly selective multiwalled nanotubes (MWNT)-Mn3O4 nano-composite catalyst was designed for liquid phase oxidation of p-cresol, which gave highest selectivity of 90% to the first step oxidation product, p-hydroxy benzyl alcohol. Mn3O4 nanoparticles and MWNT-Mn3O4 nanocomposites were synthesized by coprecipitation route using mixed precursors under controlled conditions. The phase purity of Mn3O4 and the formation of MWNT-Mn3O4 nanocomposites were confirmed by X-ray diffraction, Raman spectroscopy, and X-ray photoelectron spectroscopy. High-resolution transmission electron microscopy revealed the selective exposure of (101) and (001) planes of Mn3O4 nanoparticles in the MWNT-Mn3O4 composite, while lowering in oxidizing capacity of MWNT-Mn3O4 nanocomposite confirmed by cyclic voltametry was due to incorporation of electron rich MWNT. Thus, selectivity tuning of the new material (MWNT-Mn3O4 nanocomposite) was found to be due to alteration in both geometric as well as electronic properties. A plausible reaction pathway also has been proposed involving the predominant role of nucleophilic lattice oxygen (O2-) species due to exposure of particular crystal planes giving highest selectivity to p-hydroxy benzyl alcohol.

Solvothermal synthesis, structure, and properties of metal organic framework isomers derived from a partially fluorinated link - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2011)
Solvothermal reactions of Cu(NO3)(2) center dot 3H(2)O with 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C17H10F6O4, H(2)hfbba) and terminal monodentate ligand 3-methyl pyridine (3-picoline/3-mepy) in the presence of N, N-dimethyl formamide (DMF) and N,N-diethyl formamide (DEF) solvents gave rise to two structurally different two-dimensional (2D) fluorinated metal organic frameworks (F-MOFs). The effect of the choice of solvent has been clearly reflected in the structures obtained. The F-MOFs reported in this paper are formulated as [Cu-2(hfbba)(2)(3-mepy)(2)] center dot (DMF)(2)(3-mepy) (F-MOF-4), [Cu-2(hfbba)(2)(3-mepy)(2)] (Cu-F-MOF-4B), and [Zn-2(hfbba)(2)(3-mepy)(2)] center dot (3-mepy) (Zn-F-MOF-4B) which displays interesting 2D structures with and without interdigitation depending on the solvent used. The structures of these F-MOFs have been determined by X-ray crystallography and further identified by IR spectroscopy, powder X-ray diffraction (PXRD), and thermogravimetric analysis (TGA). The effect of interdigitation has been reflected in the gas adsorption and magnetic properties of these F-MOFs. These F-MOFs also show comparable H-2 and CO2 uptake depending on their structural variation. Temperature-dependent magnetic susceptibility measurements over a wide range of temperatures exhibit dominantly short-range antiferromagnetic behavior, with weak ferromagnetic behavior showing up at very low temperatures, which is evident from opening of the hysteresis loop with a finite value of coercivity in both F-MOF-4 and Cu-F-MOF-4B. We observed a smaller value of mu(eff) per Cu atom and coercivity in Cu-F-MOF-4B than the F-MOF-4 due to relatively larger distances between the neighboring dicopper paddlewheel secondary building unit.

Structural and gas adsorption study of a two-dimensional copper-tetrazole based metal-organic framework - Pachfule, Pradip; Banerjee, Rahul (Current Science, 2011)
A new two-dimensional (2D) metal organic framework, Cu-1(4-TBA)(1)(DMBP)(1).DMF (Cu-TBA-3), has been synthesized under solvothermal condition from transition metal cation Cu(II), predesigned ligand 4-(1H-tetrazole-5-yl)benzoic acid (4-TBA) and coligand 4,4'-dimethy1-2,2'-bipyridine (DMBP). The structure has been determined by single crystal X-ray crystallography which shows layered 2D structure with square shaped one-dimensional channels. Cu-TBA-3 shows 0.69 wt% H-2 (at 77 K, 1 atm) and 1.65 mmol/g CO2 (at 298 K, 1 atm) uptake.
Keywords: CO2 capture; Hydrogen storage; metal-organic frameworks; microporous materials

Structural and selective gas adsorption studies of polyoxometalate and tris(ethylenediamine) cobalt(III) based ionic crystals - Dey, Chandan; Das, Raja; Pachfule, Pradip; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2011)
Seven new ionic solids built on polyoxometalate anions and [Co(en)(3)](3+) cations, namely, [Co(en)(3)Mo(8)O(26)(H(3)O)-(Cl)](DMF)(4)(H(2)O) (Co-Mo(8)-DMF), [alpha-PW(12)O(40)][Co(en)(3)]center dot 6DMF (Co-W(12)P-DMF), [alpha-PW(12)O(40)][Co(en)(3)]center dot 6DEF (Co-W(12)P-DEF), [alpha-PMo(12)O(40)][Co(en)(3)]center dot 5.5DMF (Co-Mo(12)P-DMF), [alpha-PMo(12)O(40)][Co(en)(3)]center dot 6DEF (Co-Mo(12)P-DEF), [alpha-SiW(12)O(40)]-[Co(en)(3)](3/2)[Cl](1/2)center dot 6DMF center dot 3H(2)O (Co-W(12)Si-DMF), and [alpha-SiW(12)O(40)][Co(en)(3)]center dot 6DEF (Co-W(12)Si-DEF), have been synthesized from nonaqueous (DMF/DEF) media and characterized by single-crystal X-ray diffraction. We attempt to understand if [Co(en)(3)](3+) cations used in these reaction systems play a crucial role in controlling the assembly of these crystals. These ionic solids, after removal of the DMF or DEF molecules, are found to exhibit size selective H(2) adsorption properties over N(2). The amount of hydrogen adsorption was influenced by POM anion types and their orientations. CoMo(12)P-DEF has the highest (0.9 wt %) H(2) uptake, and CoW(12)P-DEF has the lowest (0.4 wt %) uptake among the series when the adsorbate pressure approached 1 atm.

Structural isomerism and effect of fluorination on gas adsorption in copper-tetrazolate based metal organic frameworks - Pachfule, Pradip; Chen, Yifei; Sahoo, Subash Chandra; Jiang, Jianwen; Banerjee, Rahul (Chemistry of Materials, 2011)
Synthesis, structure, and gas adsorption properties of three Metal Organic Frameworks (MOFs) synthesized from predesigned ligands 4-(1H-tetrazole-5-yl)benzoic acid (4-TBA) and 2-fluoro-4-(1H-tetrazole-5-yl)benzoic acid (2F-4-TBA) along with Cu(II) as an metal precursor has been reported. Among these MOFs, Cu-9(4-TBA)(10)(C2H5OH)(2) (Cu-TBA-1) and Cu-2(4-TBA)(2)(DMF)(C2H5OH) (Cu-TBA-2) are structural isomers. Whereas, Cu-2(4-TBA)(2)(DMF)(C2H5OH) (Cu-TBA-2) and Cu-2(2-F-4-TBA)(2)(DMF)(2) (Cu-TBA-2F) have similar crystal structure. N-2 adsorption isotherms of the activated sample of Cu-TBA-1 and -2 exhibit types-I sorption behavior with a Langmuir and Brunauer-Emmett-Teller (BET) surface area of 686, 402 m(2)/g and 616, 356 m(2)/g, respectively. It is noteworthy that Cu-TBA-1 and -2 adsorbs 1.16 and, 1.54 wt % H-2, while Cu-TBA-2F adsorbs 0.67 wt % at 77 K and 1 atm. On the other hand, Cu-TBA-1 and -2 adsorb 3.08 and 2.54 mmol/g, while Cu-TBA-2F adsorbs 1.27 mmol/g of CO2 at 298 K and 1 bar pressure. H-2 adsorption sites in Cu-TBA-2 and -2F have been analyzed by molecular simulation.
Keywords: CO2 adsorption; fluorination; Hydrogen storage; Metal-organic framework; structural isomerism

Structural, magnetic, and gas adsorption study of a series of partially fluorinated metal-organic frameworks (HF-MOFs) - Pachfule, Pradip; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Inorganic Chemistry, 2011)
Four new partially fluorinated metal organic frameworks (HF-MOFs) have been synthesized under different solvothermal conditions (H2O or dimethylformamide (DMF)) from transition metal cations [Co2+ and Mn2+], 3-methyl pyridine (3-mepy) and 4,4'-(hexafluoroisopropylidene) bis(benzoic acid) (C17H10F6O4, H(2)hfbba), to determine the influence of reaction conditions on the formation of MOFs. This family of materials displays a striking degree of structural similarity depending on the solvent of synthesis. HF-MOFs synthesized from H2O [Co-HFMOF-W, Co(liffiba)(3-mepy)(H2O) and Mn-HFMOF-W, Mn(hfbba)(3-mepy)(H2O)] contain three-dimensional connectivity whereas HF-MOFs synthesized from DmF Co-HFMOF-D, [Co-2(hfbba)(2)(3-mepy)(2)]center dot(DMF)(3) and Mn-HFMOE-D, [Mn-2(hfbba)(2)(3-mepy)]center dot(H2O) are two-dimensional in nature. Co-HFMOF-W and Mn-HFMOF-W are iso-structural polymeric materials. Thermal gravimetric analysis performed on as-synthesized HP-MOFs revealed that these compounds have high thermal stability (similar to 350 degrees C). The continuous decrease of the chi T product with decreasing T for Co-HFMOF-D and Co-HFMOF-W respectively indicates the presence of antiferromagnetic exchange interaction between two Co2+ (S = 3/2) metal centers within a duster.

Structure and gas sorption behavior of a new three dimensional porous magnesium formate - Mallick, Arijit; Saha, Subhadeep; Pachfule, Pradip; Roy, Sudip; Banerjee, Rahul (Inorganic Chemistry, 2011)
A new three-dimensional magnesium formate polymorph, namely, gamma-[Mg-3(O2CH)(6)] has been synthesized via in situ formate anion generation method. gamma-Mg-formate crystallizes in space group Pbcn, and structural determination by X-ray single crystal diffraction reveals a three-dimensional network of Mg2+ linked by formate anions. All formate anions possess similar binding mode to the metal center with one oxygen of a particular formate anion binds to one metal center (mu(1) oxygen) and other oxygen binds to two metal centers (mu(2) oxygen). N-2 adsorption studies indicate that the framework displays permanent porosity. The specific surface area of gamma-Mg-formate (BET, 120 m(2) gm(-1)) is lower than the alpha- polymorph (BET, 150 m(2) gm(-1)). However, the initial hydrogen uptake of gamma-Mg-formate reached almost 1.0 wt % when the adsorbate pressure approached 760 Torr at 77 K. This is higher than the hydrogen uptake of alpha-Mg-formate (0.6 wt %). gamma-Mg-formate, shows a moderate affinity and capacity for CO2 (3.4 angstrom kinetic diameter) at 298 K. The CO2 uptake at 760 Torr is 2.01 mmol gm(-1)(47.0 cc gm(-1)). Although this CO2 uptake is somewhat modest, it compares well with the CO2 uptake of several Mg-MOFs and ZIFs reported in the literature.

Syntheses, X-ray structures, catalytic activity and magnetic properties of two new coordination polymers of Co(II) and Ni(II) based on benzenedicarboxylate and linear N,N `-donor Schiff base linkers - Bhattacharya, Biswajit; Maity, Dilip Kumar; Pachfule, Pradip; Colacio, Enrique; Ghoshal, Debajyoti (Inorganic Chemistry Frontiers, 2014)
{Two isostructural coordination polymers based on Co(II) and Ni(II), {[M(azpy)(3)(p-bdc)(2)(H2O)(4)]center dot(CH3OH)(2)(H2O)(3)}(n) [where M = Co (1) and Ni (2); azpy = N,N'-bis-pyridin-4-ylmethylene-hydrazine and p-bdc = 1,4-benzenedicarboxylate], have been synthesized using mixed ligand systems at room temperature and characterized by single-crystal X-ray diffraction and other physicochemical methods. Structure determination reveals that both the complexes crystallize in the monoclinic space group C2/c and exhibit one-dimensional (1D) ladder like structures constructed by p-bdc and azpy ligands in which Schiff base (azpy) linkers serve as a bridging as well as pendent ligands. These pendent ligands are involved in H-bonding and pi-pi interactions with lattice water, methanol molecules and bridging azpy ligands, to form the 3D supramolecular structure. Notably, both the frameworks efficiently catalyze the Knoevenagel condensation reactions of a wide range of substituted benzaldehydes with active methylene compounds in heterogeneous medium under environmentally friendly conditions and the products were obtained in excellent yields. These catalysts were also found to exhibit excellent recyclability and re-usability without any significant loss of activity. A variable temperature magnetic study of both compounds was carried out and their magnetic properties justified on the basis of their crystal structure.